Comparison of Participation Constraints in Recreational Physical Activity of the Teachers Working Iğdir and Erzurum Provinces - ÖZTÜRK, Mehmet Ali (Asian Journal of Education and Training, 2019)
The aim of the study is to compare the participation constraint for leisure activities of teachers who working In the Ministry of National Education (MNE). In order to determine the leisure time constraints leisure constraints scales (LCS) were applied to the participants. A total of 413 teachers (258 male and 155 female) working in the Ministry of National Education participated in the study in Iğdır and Erzurum provinces. No statistically significant difference was found at the level of p <0,05 in any of the sub-dimensions as a result of the inter-city comparison of the female participants. While there was a significant difference in the lack of information, facilities and time sub-dimensions of the male participants in the study, p <0.05 was not significant difference in the other sub-dimensions. It is seen that the difference is in favor of the participants from the province of Erzurum. There was no statistically significant difference between the two cities in terms of lack of information, facilities and time (p <0,05) in the subscales, as in male participants. The female teachers who working Iğdır and Erzurum province there was no difference between the scores in the LCS and the mean scores of both groups were close to each other. For the male participants working in Iğdır province, it was determined that the lack of information, facilities and time constraints were more effective in participation of recreational physical activities than male participants working in Erzurum province.